Run, Rose, run - Parton, Dolly; Patterson, James, 1947- (Little, Brown and Company, 2022)
On the rise and on the run, a young singer-songwriter arrives in Nashville to claim her destiny, but it's also where the darkness she's fled might find her--and destroy her.